Dystrophin deregulation is associated with tumor progression in KIT/PDGFRA mutant gastrointestinal stromal tumors - Pantaleo, Maria A (BioMed Central, 2014)
BACKGROUND: Intragenic deletions of the dystrophin-encoding and muscular dystrophy-associated DMD gene have been recently described in gastrointestinal stromal tumor (GIST), rhabdomyosarcoma (RMS) and leiomyosarcoma (LMS). We evaluated the copy numbers and gene expression levels of DMD in our series of GIST patients who were already studied with wide genome assays, to investigate more fully a correlation between dystrophin status and disease annotations. FINDINGS: Our study highlighted a recurrent intragenic deletion on chromosome X, involving the DMD gene that codes for human dystrophin in GIST patients. Of 29 KIT/PDGFRA mutant GIST samples, 9 (31%) showed deletions of the DMD gene, which were focal and intragenic in 8 cases, and involved loss of an entire chromosome in one case (GIST_188). DMD loss was seen in only 5 patients with metastasis, whereas 18 out of 20 patients with localized disease had wild-type DMD (P = 0.0004, Fisher exact test). None of the 6 KIT/PDGFRA WT GIST showed DMD alterations. CONCLUSIONS: Our study confirms the presence of DMD deletions only in KIT/PDGFRA mutant GIST and this event is almost associated with metastatic disease. These findings are, of course, quite preliminary but support development of potential therapeutic strategies that target and restore DMD function in the treatment of metastatic GIST.